2015
DOI: 10.3168/jds.2014-9030
|View full text |Cite
|
Sign up to set email alerts
|

Dairy farm cost efficiency in leading milk-producing regions in Poland

Abstract: This paper examines the cost efficiency of dairy farms in 2 important regions of commercial milk production in Poland (i.e., Wielkopolskie and Podlaskie). Both regions gained importance following the market-driven resource allocation mechanism adopted after Poland's transition to the market economy in 1989 and accession to the European Union (EU) in 2004. The elimination of the dairy quota system in the EU in 2015 offers new expansion opportunities. The analysis of trends in cow numbers, milk production, and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Considering milk production profitability that author for the years 2003-2006and Pytlewski et al (2014 for the years 2001-2012 obtained much higher values of that index. Sobczyński et al (2015) when analysing milk production efficiency on farms in two Polish provinces: the Wielkopolskie and the Podlaskie, found that farms in those regions are capable of competing with farms of four countries being the largest milk producers in the EU. This is because of the potential for improvement of the average milk yield per cow in those two Polish provinces and thanks to the potential to reduce milk production costs.…”
Section: Discussionmentioning
confidence: 99%
“…Considering milk production profitability that author for the years 2003-2006and Pytlewski et al (2014 for the years 2001-2012 obtained much higher values of that index. Sobczyński et al (2015) when analysing milk production efficiency on farms in two Polish provinces: the Wielkopolskie and the Podlaskie, found that farms in those regions are capable of competing with farms of four countries being the largest milk producers in the EU. This is because of the potential for improvement of the average milk yield per cow in those two Polish provinces and thanks to the potential to reduce milk production costs.…”
Section: Discussionmentioning
confidence: 99%
“…Even before the cancelation dairy quota abolishment had attracted the attention of many studies, many of them were focused just on the situations in one or two countries. It can be said that some authors predicted an increase in milk supply together with decreasing prices for producers [18,35] as well as increasing competitiveness both within states [14] and globally [36]. The dairy sector was expected to be more dynamic than before the quota elimination [37], with a strong increase in intensity for the largest farms [1,20] with ultimately a slightly positive welfare effect [38].…”
Section: Of 21mentioning
confidence: 99%
“…As stated by Philippidis and Waschik [11], technological change is connected with structural change and has an effect on both the agricultural milk production sector and the dairy processing sector, in perfect competition as well as imperfect competition. Sobczyński et al [14] consider the use of advanced technology to be a key factor in achieving a higher yield per cow in a chosen region of Poland, and, according to Žáková Kroupová et al [15], it influences the total factor productivity change.…”
Section: Introductionmentioning
confidence: 99%
“…The variable assumes the value of 1 for all observations falling in the period after the milk quota system expired. Many Polish dairy farms were preparing themselves for the expansion of milk production long before the system was abolished [34], and they were even ready to pay fines for exceeding the allocated quota [35]. The study empirically tests the actual effect of quota termination on butter and curd prices in two regions.…”
Section: Modeling Approachmentioning
confidence: 99%